2016
DOI: 10.3389/fpls.2016.01630
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Long-Term Corn Yield Response to Nitrogen Rate and Crop Rotation

Abstract: Improved prediction of optimal N fertilizer rates for corn (Zea mays L.) can reduce N losses and increase profits. We tested the ability of the Agricultural Production Systems sIMulator (APSIM) to simulate corn and soybean (Glycine max L.) yields, the economic optimum N rate (EONR) using a 16-year field-experiment dataset from central Iowa, USA that included two crop sequences (continuous corn and soybean-corn) and five N fertilizer rates (0, 67, 134, 201, and 268 kg N ha-1) applied to corn. Our objectives wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 112 publications
(155 reference statements)
5
79
0
Order By: Relevance
“…Stanford (1973) himself acknowledged that this approach "… largely ignores the dynamic nature of the water-soil-plantnitrogen system". Dynamic simulation models of soil and crop processes have the potential for estimating N dynamics and crop fertilizer needs (Melkonian, van Es, DeGaetano, Sogbedji, & Joseph, 2007;Puntel et al, 2016;Setiyono et al, 2011). Recently, the performance of the dynamic-adaptive Adapt-N simulation tool (Melkonian, van Es, DeGaetano, & Joseph, 2008;van Es et al, 2007b) was evaluated on commercial farms against a Stanford-type method and a static empirical approach known as the Maximum Return To N (Sawyer et al, 2006).…”
Section: Core Ideasmentioning
confidence: 99%
“…Stanford (1973) himself acknowledged that this approach "… largely ignores the dynamic nature of the water-soil-plantnitrogen system". Dynamic simulation models of soil and crop processes have the potential for estimating N dynamics and crop fertilizer needs (Melkonian, van Es, DeGaetano, Sogbedji, & Joseph, 2007;Puntel et al, 2016;Setiyono et al, 2011). Recently, the performance of the dynamic-adaptive Adapt-N simulation tool (Melkonian, van Es, DeGaetano, & Joseph, 2008;van Es et al, 2007b) was evaluated on commercial farms against a Stanford-type method and a static empirical approach known as the Maximum Return To N (Sawyer et al, 2006).…”
Section: Core Ideasmentioning
confidence: 99%
“…Many surveys have reported that most of the producers overestimate the target yield to determine the N requirement [48]. Similarly, studies in Wisconsin [49], Pennsylvania [50], and Ontario [51] have shown the problems of using yield expectation to predict N rate and consequently raise concern over its reliability and use for future N recommendations.…”
Section: Soil Test Approachmentioning
confidence: 99%
“…Over the past years the APSIM model has been successfully applied in this region to simulate production (Hammer et al, 2009;Archontoulis et al, 2014a, b;Dietzel et al, 2016;Puntel et al, 2016;Jin et al, 2017) and environmental aspects of US Midwestern corn and soybean cropping systems (Malone et al, 2007;Archontoulis et al, 2016a, b;Basche et al, 2016;Martinez-Feria et al, 2016).…”
Section: The Apsim Model Description and Configurationmentioning
confidence: 99%
“…While there are many physically-based cropping system model platforms available (APSIM; Holzwort et al, 2014), Decision Support System for Agrotechnology Transfer (DSSAT; Jones et al, 2003;Hoogenboom et al, 2015), System Approach to Land Use Sustainability (SALUS; Basso et al, 2010Basso et al, , 2012), we chose to use APSIM based on the combination of numerous detailed calibrations previously conducted in our region (Hammer et al, 2009;Malone et al, 2009;Archontoulis et al, 2014a, b;Archontoulis et al, 2016a, b;Basche et al, 2016;Dietzel et al, 2016;Jin et al, 2016;Martinez-Feria et al, 2016;Puntel et al, 2016) and the wide range of realistic in-season management options available such as when to apply fertilizer, spray chemicals, and harvest (Horie et al, 1992;Lawless & Semenov 2005;Howden et al, 2007).…”
Section: Reasons For Over/under Predictions Of Crop Yields During Thementioning
confidence: 99%